MATHEMATICAL LITERACY ABILITY OF STUDENTS FROM A COGNITIVE STYLE PERSPECTIVE ON RATIONAL NUMBERS - Yusfita Yusuf; Yuni Nurfitriani; Ucu Koswara (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
This study aims to describe mathematical literacy skills reviewed from cognitive styles of studdents. This study is a descriptive research with a qualitative approach. The subjects of this study consist of 4 students in grade VII A SMP Negeri 1 Ganeas in the odd semester for the 2023/2024. The instruments used in this study were a mathematical literacy ability test, the Group Embedded Figure Test (GEFT) test to find out the type of student cognitive style, and interview guidelines. The results of this study show that students with a field independent cognitive style have better mathematical literacy abilities than field dependent ones. Field independent students met almost all levels of mathematical literacy indicators, while field dependent students only met 3 levels of mathematical literacy abilities